РОЛЬ МЕНЕДЖЕРА В РЕАЛІЗАЦІЇ ЗМІН - Kaschuck, Kateryna (Zhytomyr Ivan Franko State University, 2025)
The successful implementation of organizational changes largely depends on the capabilities of the managers who manage them. The purpose of this article is to defend the idea of the need to appoint change management managers in the organization, to identify the significance of this position and to analyze their functions. The article examines the key role of the manager in the process of implementing organizational changes. It is noted that the success of transformations in modern companies largely depends on the competence, leadership qualities and professional experience of managers responsible for changes. The emphasis is on the need to introduce a special position of the change management manager, which allows forming a culture of constant innovation and flexibility in the organization. The main functions of such a manager are revealed: diagnosing problems, developing a change strategy, overcoming resistance, coordinating team actions and evaluating the results of transformations. Typical sources of resistance to change at both the organizational and personal levels are separately analyzed, including the company structure, organizational culture, fear of losing status, uncertainty, distrust of management and lack of motivation. It is determined that effective change management requires not only rational planning, but also active work with personnel, involving employees in the decision-making process, support from senior management and established communication. It is emphasized that the change management manager should be an agent of transformation, able to inspire the team, develop innovative thinking and form an environment of trust. The article also considers different approaches to the appointment of a change manager, namely: internal appointment, involvement of an external consultant or a combination of these models. It is concluded that only a systematic and flexible approach to change management ensures the competitiveness of the organization and its sustainability in modern conditions. It has been established that a systematic approach, constant monitoring and readiness to respond to unforeseen situations ensure the successful achievement of the desired future state of the organization. Change management is an organizational process aimed at helping people understand and accept new working conditions, which is the key to business development and competitiveness.